Implementasi Model Pembelajaran Project Based Learning (PjBL) Berbantuan Powerpoint Interaktif untuk Meningkatkan Minat dan Hasil Belajar Matematika Siswa SMK - Dinda Qori Wahyuni; Nurdalilah Nurdalilah; Nurhafni Siregar; Wilda Hasanah; Elsadday Br Manalu (Journal on Education, 2024)
This research is based on the low interest in studying mathematics in class The type of research used is Classroom Action Research (PTK). The subjects in this classroom action research were 35 students of class X ULP 1 SMK Negeri 7 Medan consisting of 8 male students and 27 female students. The instruments used in this research were observation sheets of student and teacher learning activities, student interest questionnaires and test sheets. Based on the results of research that has been carried out in two cycles in this study, it is concluded that the application of the project based learning (PjBL) learning model with the help of interactive PowerPoint can increase students' interest in learning statistics. This can be seen from the increase in students' interest in learning from before the research was carried out (pre cycle) amounting to 48.2% (Poorly Good) to 73.38% (Good) after the first cycle and increasing again after the second cycle, amounting to 81.6% (Very good). Student statistics learning outcomes also increased from before the research was conducted (pre-cycle) by 50.8% (Poorly Good) to 73.73% (Good) after the first cycle and increased again after the second cycle of 81.30% (Very Good ).